Opposition & intimidation : the abortion wars & strategies of political harassment - Doan, Alesha E., 1972- (The University of Michigan Press, 2007)
Annotation : The abortion fight has long been a crucible of political tactics, with both sides employing strategies ranging from litigation to civil disobedience to outright violence. Anti-abortion activists have arguably been more tactically innovative than their pro-choice peers. Opposition and Intimidation looks at how their use of political harassment fits or doesn't with more conventional political efforts in the struggle over abortion. Alesha Doan's insightful interviews and observations powerfully portray anti-abortion activists' relationship to the objects of their protest. Her portrait is augmented by thorough quantitative analysis of harassment's role within the movement's multitiered strategy a strategy that Doan shows has forced a decline in the availability and popularity of abortions. Using her unique study of the anti-abortion movement as a model, Doan extends her findings to propose a novel and valuable theory of the new politics of harassment. An interesting and sophisticated account. Seamlessly weaves narrative and analysis, tying local action to national strategy. Explores uncharted territory in the abortion controversy and expands our understanding of political action." "For 40 years, abortion politics have been endlessly fascinating to American scholars and journalists alike because they generate unique political phenomena that challenge traditional theories of political behavior. In this book, Doan goes straight to the heart of the matter by describing, evaluating, and explaining one of the most characteristic and complex of these phenomena political harassment. In a well-written narrative that weaves qualitative and quantitative data, she gives us the first scholarly look at this political tactic, whose relevance and use go well beyond American abortion politics." Chris Mooney, University of Illinois at Springfield "The book contributes to political theory and knowledge by adding new empirical data gathered from interviews with those in the front lines of the struggle over abortion. The author refines and develops a category of unconventional political participation political harassment of nongovernmental actors and explains why it is particularly effective in undermining the rights of women seeking abortions, as well as the rights of abortion service providers." Nikki R. Van Hightower, Texas A & M University Alesha E. Doan is Assistant Professor of Political Science at the University of Kansas -- Provided by publisher